2005
DOI: 10.1007/s11255-004-1466-0
|View full text |Cite
|
Sign up to set email alerts
|

Focal Segmental Glomerulosclerosis in Kidney Resected for Renal Cell Carcinoma

Abstract: A diagnosis of renal dysfunction is usually made on the basis of clinical, biochemical, radiologic, and renal tissue analysis. Accurate diagnosis often requires a renal biopsy, but that procedure is contraindicated in certain clinical circumstances, particularly in patients who have only one kidney. We describe a patient who previously had undergone left nephrectomy for a renal clear cell carcinoma, in whom the diagnosis of focal segmental glomerulosclerosis was made on retrospective analysis of remnant renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Magyarlaki et al [21] reported 5 cases (8%) of focal segmental glomerulosclerosis in 60 autopsy cases of renal cell carcinoma, however, there are only a few reports of focal segmental glomerulosclerosis with renal cell carcinoma [52] and Wilms' tumor [53]. Glomerulosclerotic lesions are often observed in the renal parenchyma adjacent to a tumor, so parenchymal compression and urinary outflow obstruction by renal tumor may be involved in the development of focal segmental glomerulosclerosis.…”
Section: Minimal Change Disease and Focal Segmental Glomerulosclerosimentioning
confidence: 99%
“…Magyarlaki et al [21] reported 5 cases (8%) of focal segmental glomerulosclerosis in 60 autopsy cases of renal cell carcinoma, however, there are only a few reports of focal segmental glomerulosclerosis with renal cell carcinoma [52] and Wilms' tumor [53]. Glomerulosclerotic lesions are often observed in the renal parenchyma adjacent to a tumor, so parenchymal compression and urinary outflow obstruction by renal tumor may be involved in the development of focal segmental glomerulosclerosis.…”
Section: Minimal Change Disease and Focal Segmental Glomerulosclerosimentioning
confidence: 99%